Medico-financial Environment on Treatment for Acutely Ruptured Cerebral Aneurysms: GDC Embolization vs Neck Clipping - Koguchi, Y. (Centauro S.r.l., 2004)
We have been using the Guglielmi detachable coils (GDC) since 1997 as one choice of cerebral aneurysm treatment. We have, at the present time, two effective radical treatment methods for acutely ruptured cerebral aneurysms, GDC embolization and conventional surgical aneurysmal neck clipping. There ensued questions about the cost and efficacy of the two strategies. Retrospective analysis was done on a GDC group and a clipping group, with each twenty consecutive patients. The features of the GDC group patients were higher age, and poorer Hunt and Kosnik grades than the other group. All MCA aneurysms were treated with surgical neck clipping, while all the posterior circulation aneurysms were embolized with GDC. Based on the Japanese Medical Insurance and Payment System, 477,890 points (1 point = ￥10) as a mean was required with the GDC group, and 456,084 points with the neck clipping group, showing no significant difference between the two groups. In the GDC group, the cost of the implanted medical device seemed to raise the total medical expense. At present, the GDC embolization is the preferred choice of strategies in acutely ruptured cerebral aneurysms, and its preference increases in the surgically difficult cases, very old, or poor grade patients, and in various complicated cases. And, the GDC embolization seems to be satisfactory from the medico-financial viewpoint.